Novel regulators of T helper cell differentiation con-tribute to autoimmune inflammation - Mohammad, Imran (fi=Turun yliopisto|en=University of Turku|, 2018)
T helper cells are critical components of adaptive immune system contributing to self/ nonself-recognition, pathogen elimination and pathogenesis of immune-associated diseases. Understanding the underlying mechanisms and signaling changes associated with T cell differentiation and autoimmune inflammatory disease processes remains far from being complete. The studies presented in this PhD thesis were aimed to investigate the role of a suspected/known contributor to autoimmune inflammation and to identify novel modulators that regulate Th17 and iTreg cell differentiation. Autoimmune diseases show greater predominance in females than in males and the underlying mechanisms of this are not well understood. In this study, the role of estrogen receptor alpha (ERα) in the development of autoimmune T cell responses has been addressed. T cell specific ERα depleted mice were induced to develop a T cell mediate autoimmune disease. The results indicated that ERα contributes to autoimmune inflammation, T cell activation, proliferation, and survival. Additionally, in regulatory T cells the ERα protein was observed to regulate the expression of Foxp3. The results of this study provide insight into understanding the role of estrogen receptor in autoimmune diseases and also provide implications for the development of novel therapeutics. To further identify novel regulators of Th17 and iTreg cell differentiation, a label-free quantitative proteomics approach was applied to profiling the protein expression changes from whole Th17 and iTreg cells. Selected proteins that showed expression changes during Th17 and iTreg cell differentiation were validated. Proteomic and transcriptomic data was combined to identify the proteins that are differentially regulated in Th17 or iTreg cells only at protein level. The work presented in this thesis provides an insight into the proteome of important T helper cell subsets with further implications for further development of novel therapies to treat autoimmune diseases.

T-solujen erilaistumiseen vaikuttavat uudet säätelijät osallistuvat autoimmuunitulehdukseen T-auttajasolut ovat olennainen osa hankittua immuunijärjestelmää, jossa ne toimivat mukana oma- ja vierasperäisten tekijöiden tunnistamisessa, taudinaiheuttajien tuhoamisessa ja tiettyjen sairauksien immuunireaktioissa. T-solujen erilaistumiseen ja autoimmuunitulehdussairauksien kehittymiseen vaikuttavien mekanismien ja signaalireittien muutosten ymmärtäminen on yhä kaukana kokonaisvaltaisesta kuvasta. Kyseisen tohtorikoulutustutkimuksen tavoitteena oli tutkia autoimmuunitulehdukseen vaikuttavaa tekijää sekä tunnistaa uusia proteiineja, jotka säätelevät auttaja-T-17- solujen (Th17) ja indusoitujen säätelijä-T-solujen (iTreg) erilaistumista. Autoimmuunisairaudet ovat yleisempiä naisilla kuin miehillä ja sen perustana olevat mekanismit eivät ole selvitetty. Ensimmäisen tutkimuksen kohteena oli estrogeenireseptori- alfan (ERα) rooli T-soluvälitteisten autoimmuunisairauksien kehittymisessä. ERα-puutteiset T-solut hiiressä altistettiin T-soluvälitteisille autoimmuunisairauksille. Tulokset osoittavat että ERα vaikuttaa tulehdukseen sekä solujen aktivaatioon, jakautumiseen ja selviytymiseen. ERα-puutteiset T-solut osoittavat Foxp3 proteiinin kohonnutta ilmenemistä. Tulokset selvittävät hormonireseptorien roolia autoimmuunisairauksissa sekä niiden käyttömahdollisuutta uusien hoitomenetelmien kehityksessä. Uusien Th17- ja iTreg-solujen erilaistumiseen vaikuttavien säätelijöiden tunnistamiseksi käytettiin merkkiaineetonta ja kvantitatiivista proteomiikkamenetelmää. Proteiinien ilmenemismuutokset profiloitiin Th17- ja iTreg-solujen eri osista ja valitut proteiinit varmistettiin lisäkokeilla. Proteomiikka ja transkriptomiikkatuloksia verrattiin keskenään näissä eri tavoin käyttäytyvien solun proteiinien tunnistamiseksi. Tutkimus tuotti arvokasta aineistoa uusien hoitomenetelmien kehitykseen autoimmuunisairauksissa.